Curriculum Management in The Era of Industrial Revolution 4.0: A Literature Analysis of Curriculum Change and Adaptation - Darmawati; Pulungan, Lilik Hidayat (JTP - Jurnal Teknologi Pendidikan, 2025)
The development of the Industrial Revolution 4.0 requires the education system to continue to adapt to technology and dynamic social changes. The curriculum as the foundation of education undergoes various changes to adapt to industry needs and global demands. This research aims to analyze curriculum changes in Indonesia through literature studies, focusing on the comparison between the 2013 Curriculum, Merdeka Curriculum, and the latest National Curriculum. The method used is a bibliometric approach with data analysis from various academic and educational policy sources. The results show that Curriculum 2013 still tends to be rigid and less flexible, while Merdeka Curriculum provides more freedom in learning design. The new National Curriculum is designed to integrate digital technology and 21st century skills but is still in the early stages of implementation. The impact of these changes on teachers includes increased demands on digital and pedagogical competencies, while for students, a more flexible curriculum provides learning opportunities that are more suited to individual needs. The study recommends improved teacher training, equitable distribution of digital infrastructure and collaboration between schools, industry and government in curriculum design.